Bioactive pigment production by Pseudomonas spp. MCC 3145: Statistical media optimization, biochemical characterization, fungicidal and DNA intercalation-based cytostatic activity. (July 2017) - Patil, Sandeep; Nikam, Monali; Patil, Hemangi; Anokhina, Tatyana; Kochetkov, Vladimir; Chaudhari, Ambalal
Graphical abstract: Highlights: PYC production was increased 18-fold using statistical tools (PBD and CCD). Fine structural details of PYC were confirmed using bioanalytical techniques. PYC showed significant fungicidal activity against several phytopathogens. PYC demonstrated cytostatic activity against four major cancer cell lines. PYC showed nonspecific DNA intercalation activity. Abstract: Multifunctional redox-active pyocyanin (PYC) produced by Pseudomonas aeruginosa has diverse biotechnological applications, but no efforts have been made to improve its yield. The yield obtained in initial study using Pseudomonas spp. MCC 3145 was 24.21 mg L −1 PYC in pigment production medium D; hence, optimization of the media components using statistical tools for more production of PYC was undertaken. Of the 11 medium constituents screened for PYC production using Plackett–Burman design (PBD), glycerol, peptone, and CuSO4 were recognized as the most significant variables. The optimal concentration of the variables for maximum PYC production was evaluated using a five-level three-factor central composite design (CCD). Optimal concentration of the three variables, glycerol, peptone and CuSO4 showed 313.94 ± 10.09 mg L −1 the PYC production, with an 18-fold increase. Fine structural details of PYC were verified by chromatographic and various spectroscopic analyses. In vitro bioactivity studies demonstrated significant antifungal activity of PYC against fungal phytopathogens and substantial cytostatic activity against four major cancer cell lines. Furthermore, PYC displayed nonspecific DNA intercalation, which may be the reason for proliferation arrest in cancer cells. Thus, the study rigorously improved PYC production through medium optimization and further demonstrated its agricultural and therapeutic applications.